2019
DOI: 10.20944/preprints201906.0041.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data-Driven Bicycle Network Analysis Based on Traditional Counting Methods and GPS Traces from Smartphone

Abstract: This research describes numerical methods to analyze the absolute transport demand of cyclists and then to quantify the road network weaknesses of a city with the aim to identify infrastructure improvements in favor of cyclists. The methods are based on a combination of bicycle counts and map-matched GPS traces and are demonstrated with the city of Bologna, Italy: the dataset is based on approximately 27,500 GPS traces from cyclists, recorded over a period of one month on a volunteer basis using a smartphone a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
(31 reference statements)
0
5
0
2
Order By: Relevance
“…For the following investigation, two different attribute vectors have been taken into consideration: the attribute vector with a constant exclusive bikeway xaC=La,Bathickmathspace and xaP=La,LaBa where the exclusive bikeway attribute is proportional to the link length La, in accordance with other studies [4, 8, 27].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the following investigation, two different attribute vectors have been taken into consideration: the attribute vector with a constant exclusive bikeway xaC=La,Bathickmathspace and xaP=La,LaBa where the exclusive bikeway attribute is proportional to the link length La, in accordance with other studies [4, 8, 27].…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, many studies deal with the identification of road attributes that affect the cyclists’ path choice and different models have been calibrated to quantify their respective influence [2–10]. In particular, the studies in [3, 6–10] have compared the cyclist's route choice with the shortest route in order to find attributes that cause the users to deviate from the shortest path: for example, in [10] the shortest path has been used to split the global positioning system (GPS) recorded traces in a set of detour‐classes. Moreover, Rupi et al [8] calibrated a binominal logit‐model able to predict if a cyclist will choose either the shortest route or a non‐overlapping alternative, based on route‐links attributes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have proposed map matching methods to estimate unknown trajectories on roads due to the accuracy of GPS logs, based on the geometric or topological similarity with the road network and the hidden Markov models [31]. Rupi et al [32] showed that cyclists' GPS traces matched to road networks dedicated to bicycle travel correlated highly with the cyclists' flows based on manual surveys. However, the map matching process often requires large-scale computational resources [33].…”
Section: Step 3: Interpolating Points Between Observation Pointsmentioning
confidence: 99%